Democratic Professionalism in Public Services - Lethbridge, Jane (Book collections on Project MUSE., 2019)
This book explores what it means to act in a democratic way and provides practical guidance which will help public service professionals ensure users are at the centre of public services delivery, drawing from examples of different public services around the world.